The Effect Of Consumer Decision Making Style On Consumer Satisfaction And Repurchase Intention In Buying Sneakers Products Online In Indonesia - I Made Bagus Suryawan; Pujianto Yugopuspito (Enrichment : Journal of Management, 2022)
The technology development and the growth of internet users are running very fast. The increase in internet users affects the shopping behavior of Indonesian consumers where everything is done digitally, such as online shopping for the fashion sector, specifically sneakers, so many online shops have emerged that sell sneakers. This study aims to analyze the effect of consumer decision-making style on consumer satisfaction and repurchase intention in purchasing sneakers online in Indonesia. In analyzing consumer decision-making style, a measurement instrument is used, namely consumer style inventory which has 8 variables and is used as an independent variable. Consumer satisfaction is used as the intervening variable and repurchase intention is the dependent variable. This study uses quantitative research methods with PLS-SEM data analysis. Respondents were collected by the accidental sampling of people on the big islands of Indonesia who had shopped for sneakers online. 196 respondents met the requirements using a questionnaire with a Linkert scale. The results show that habitual style, novelty style, recreational style, and perfectionist style positively influence consumer satisfaction. Brand consciousness style, price-conscious style, impulsiveness style, and confused by over choice style have no positive effect on consumer satisfaction. Meanwhile, consumer satisfaction has a dominant positive effect on repurchase intention.